Calcium sulphoaluminate modified Portland cement preparation method based on thermodynamic calculation
Optimizing the ratio of calcium sulfa aluminate modified silicate cement through Gibbs energy minimization thermodynamic simulation software, solving the problems of low efficiency and high cost in traditional formulation technology, and achieving efficient and low-cost calcium sulfa aluminate modification The design of silicate cement improves early and late strength and reduces limestone consumption and CO2 emissions.
Patent Information
- Application Number
- CN202411247113.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-14
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-27
AI Technical Summary
The traditional calcium sulfa aluminate modified silicate cement preparation technology relies on trial and error methods, which is costly and inefficient, making it difficult to accurately match the ratio of sulfate and calcium sulfa aluminate to optimize performance.
The evolution process diagram of the hydration products of the calcium hydroxide-calcium sulfa-anhydrate-anhydrate gypsum ternary system was established by using Gibbs Energy Minimization Thermodynamic Simulation Software (GEMS) over time, and the calculation was determined by determining the anhydrous gypsum/calcium sulfa-aluminate The molar ratio of silicate clinker, sulfur aluminate clinker and anhydrous gypsum is optimized to improve design efficiency and performance.
It significantly improves design efficiency, reduces trial and error costs, improves early and late strength, reduces limestone consumption and CO2 emissions, is suitable for 3D-printed concrete, and reduces the amount of gelled materials.
Smart Images

Figure CN119191737A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a preparation method of calcium sulphoaluminate modified silicate cement based on thermodynamic calculation. Background Art
[0002] The CO2 emissions from the cement industry account for 8% of the total CO2 emissions from human activities. At the same time, about 63% of the CO2 emissions in the cement industry come from the decomposition of limestone in the cement production process. Especially in the production process of Portland cement clinker, more limestone needs to be calcined, and the amount of CO2 emitted is also large. Therefore, the development of non-Portland cement systems is of great significance to energy conservation and emission reduction in the construction industry. Compared with Portland cement, sulphoaluminate cement requires less limestone to be calcined, and the calcination temperature is 100℃~150℃ lower, which can reduce energy consumption by 27%~37%, and accordingly, reduce CO2 emissions by 18%~48%. Portland cement is widely used because of its advantages such as fast setting and hardening, high early strength and late strength, good frost resistance, good carbonization resistance and good wear resistance. Sulphoaluminate cement has the advantages of high frost resistance, good corrosion resistance, high impermeability and high early strength, and is widely used in emergency repair and repair projects, low temperature construction projects, and seawater corrosion resistance projects.
[0003] As researchers gradually deepen their research on cement chemistry theory and improve detection methods, people have begun to work on compounding two or more cements, aiming to combine the advantages of the two cements to prepare a composite cementitious system with excellent comprehensive performance, reduce limestone consumption, and reduce carbon emissions. However, in the design process of calcium sulfoaluminate modified silicate cement, it is unknown how much sulfate is needed to match calcium sulfoaluminate. Previous researchers have used orthogonal test methods to test the optimal anhydrous gypsum dosage, which is inefficient and costly.
[0004] The present invention is proposed in order to maximize the efficiency in the mineral phase design process of calcium sulphoaluminate modified silicate cement while maximizing the performance. Summary of the invention
[0005] Purpose of the invention: Traditional cement mix design methods are mostly based on trial and error, which is costly and inefficient. In view of the shortcomings of the existing calcium sulfoaluminate modified silicate cement preparation technology, the purpose of the present invention is to provide a low-cost and high-efficiency calcium sulfoaluminate modified silicate cement preparation method based on thermodynamic calculation.
[0006] Technical solution: A method for preparing calcium sulphoaluminate modified silicate cement based on thermodynamic calculation of the present invention comprises the following steps:
[0007] Calcium sulphoaluminate modified silicate cement is composed of silicate clinker, sulphoaluminate clinker and anhydrous gypsum;
[0008] By using Gibbs Energy Minimization Software (GEMS), a process diagram of the evolution of hydration products of the calcium hydroxide-calcium sulfoaluminate-anhydrous gypsum ternary system over time was established, and it was found that when the molar ratio of anhydrous gypsum / calcium sulfoaluminate was M=8, no monosulfur-type hydrated calcium sulfoaluminate was generated in the hydration products; based on the fact that calcium hydroxide is obtained by hydration of C3S and C2S, anhydrous calcium sulfoaluminate is provided by sulfoaluminate clinker, and based on the measured mineral phase composition of a certain silicate cement clinker and a certain sulfoaluminate cement clinker, the proportion of calcium sulfoaluminate-modified silicate cement can be inversely calculated, and the proportions of silicate clinker, sulfoaluminate clinker and anhydrous gypsum can be determined.
[0009] Furthermore, a process diagram of the evolution of hydration products of the calcium hydroxide-calcium sulfoaluminate-anhydrous gypsum ternary system over time was established using Gibbs Energy Minimization Software (GEMS).
[0010] Furthermore, the silicate clinker does not contain gypsum; the sulphoaluminate clinker contains gypsum.
[0011] Furthermore, the calcium sulphoaluminate content in the sulphoaluminate clinker exceeds 60 wt.%.
[0012] Furthermore, the specific surface areas of silicate clinker are 350m 2 / kg~450m 2 / kg, D 50 It is 10μm~50μm.
[0013] Furthermore, the specific surface areas of sulphoaluminate clinker are 350m 2 / kg~450m 2 / kg; D 50 It is 10μm~50μm.
[0014] Furthermore, the calcium sulphoaluminate modified silicate cement of the present invention is prepared by uniformly mixing silicate clinker, sulphoaluminate clinker and anhydrous gypsum in a certain proportion, and the required performance can be obtained by adjusting the invention formula according to application requirements. The calcium sulphoaluminate modified silicate cement is composed of three major components, and the proportions are:
[0015] Silicate clinker: 65wt.%~75wt.%
[0016] Sulphoaluminate clinker: 10wt.%~30wt.%
[0017] Anhydrous gypsum: 5wt.%~25wt.%
[0018] Furthermore, the standard mortar for strength test of calcium sulphoaluminate modified silicate cement is prepared by the following method: weighing raw materials; mixing silicate clinker, sulphoaluminate clinker and anhydrous gypsum, and then adding water and sand in sequence, and mixing evenly to obtain mortar.
[0019] Specifically, weigh the raw materials according to the designed ratio: put the weighed powder into a stirring pot and dry-stir at a low speed for 3 minutes; then pour water into the stirring pot at one time, stir at a low speed for 30 seconds, add sand during the process of stirring at a low speed for 30 seconds, and then stir at a high speed for 30 seconds. Stop for 90 seconds to scrape off the mortar on the side wall of the stirring pot, and then stir at a high speed for 60 seconds to obtain a uniformly mixed new mortar.
[0020] In the above scheme, the stirring container is a cement mortar stirring pot recommended in GB / T 17671, the low-speed stirring speed is 140r / min, and the high-speed stirring speed is 285r / min.
[0021] After the calcium sulphoaluminate modified-silicate mortar is prepared, it is placed in an environment with a relative humidity of ≥95% and a temperature of 20°C±2°C for curing.
[0022] Specifically, the preparation method of calcium sulphoaluminate modified silicate cement based on thermodynamic calculation comprises the following steps:
[0023] (1) Weigh the required raw materials such as silicate clinker, sulphoaluminate clinker and anhydrous gypsum according to the designed formula ratio of M value of 2 to 10, and stir for 1 minute to mix them evenly;
[0024] (2) The water-cement ratio is 0.5. Water is slowly added to the powder mixed evenly in step (1). Standard sand specified in GB / T 17671 "Test Method for Strength of Cement Mortar (ISO Method)" is added during the stirring process. The mass ratio of cement to standard sand is 1:3. Then, high-speed stirring is performed in a high shear mode for 2 minutes to form a plastic slurry, which is poured into a mold and subjected to standard curing.
[0025] (3) After demoulding, place the mortar in a standard curing box and cure it at 20°C ± 1°C and 95% ± 1% RH for 1d, 3d, 7d and 28d. Then, test the mortar strength in accordance with GB / T 17671 “Test method for strength of cement mortar (ISO method)”.
[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: The present invention uses GEMS thermodynamic simulation software to calculate the mix ratio of calcium sulfoaluminate modified silicate cement with different M values, which greatly improves the design efficiency and reduces the trial and error cost compared to the trial and error method or orthogonal test method used in the traditional cement mix design process. Since more anhydrous gypsum is introduced into the composition of calcium sulfoaluminate modified silicate cement, a large amount of calcium sulfoaluminate can be generated in the early stage compared to traditional silicate cement, which can increase the early strength by about 50%.
[0027] Due to the large amount of sulfate introduced into calcium sulfoaluminate modified silicate cement, there is almost no monosulfur hydrated calcium sulfoaluminate in the hydration products of calcium sulfoaluminate modified silicate cement, which greatly improves the later strength. If this method is used to design and prepare calcium sulfoaluminate modified silicate cement, on the one hand, it can greatly improve the design efficiency and reduce the cost of trial and error; on the other hand, sulfoaluminate partially replaces silicate cement, which can reduce the carbon dioxide emissions caused by the production of silicate cement. At the same time, due to the significant improvement in early strength and shortened setting time, it can be considered for use in 3D printed concrete. In addition, due to the improvement in strength grade, the amount of cement and other cementitious materials can be greatly reduced while maintaining the same strength grade. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a diagram showing the evolution of hydration products of calcium sulfoaluminate modified silicate cement over time;
[0029] Figure 2 is a graph of the compressive strength of the mortar of Examples 1-5;
[0030] Figure 3 Thermogravimetric analysis diagrams of Examples 1-5. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0032] In this embodiment, the silicate clinker specific surface area used is 380m 2 / kg; the specific surface area of sulphoaluminate clinker is 362m 2 / kg; the specific surface area of anhydrous gypsum is 465m 2 / kg. The mixing water is deionized water.
[0033] It should be noted that a method for preparing calcium sulphoaluminate modified silicate cement based on thermodynamic calculation includes the following main steps:
[0034] Step 1: First, using GEMS thermodynamic simulation software, a process diagram of the evolution of hydration products of the calcium hydroxide-anhydrous calcium sulfoaluminate-anhydrous gypsum ternary system over time is established, and it is found that when the molar ratio of anhydrous gypsum / anhydrous calcium sulfoaluminate is M=8, no monosulfur type calcium sulfoaluminate hydrate is generated in the hydration product.
[0035] Step 2: Since calcium hydroxide is generated by hydration of C3S and C2S in silicate clinker, anhydrous calcium sulphoaluminate is the main component phase in sulphoaluminate clinker. Based on this, the composition ratio of silicate cement, sulphoaluminate cement and anhydrous gypsum in calcium sulphoaluminate modified silicate cement is obtained by reverse calculation.
[0036] Step 3: Five groups of calcium sulfoaluminate-modified silicate cement with different M values were designed. When M=8, the compressive strength of the calcium sulfoaluminate-modified silicate mortar was the highest. Through Examples 1 to 5, the compressive strength at different curing ages was tested, and the rationality of the thermodynamic calculation design was verified. Finally, calcium sulfoaluminate-modified silicate cement with high mechanical strength, low porosity and good stability was prepared.
[0037] Embodiment 1~5:
[0038] A method for preparing calcium sulphoaluminate modified silicate cement based on thermodynamic calculation comprises the following steps:
[0039] 1) Weighing of raw materials: weigh each raw material according to the ratio described in Table 1;
[0040] 2) Put the weighed powder into a stirring pot and stir at low speed for 3 minutes;
[0041] 3) Pour the water into the mixing pot at once, stir at low speed for 30 seconds, add sand during the process of stirring at low speed for another 30 seconds, stir at high speed for another 30 seconds, stop for 90 seconds to scrape off the mortar on the side wall of the mixing pot, and stir at high speed for another 60 seconds to obtain a uniformly mixed new mortar.
[0042] The compressive strength test of Examples 1 to 5 was carried out with reference to GB / T 17671 "Test Method for Cement Mortar Strength (ISO Method)". The test results are as follows: Figure 1 shown. Figure 1 is the compressive strength of calcium sulfoaluminate modified silicate cement under different M values. Figure 1 It can be seen that when M = 2, the mortar compressive strength of the system at 1d, 3d, 7d and 28d is 6.5MPa, 12MPa, 19MPa and 25.2MPa respectively, and the early strength and late strength are very low. In order to further analyze the reasons, the TG-DTG curve of the sample was tested, such as Figure 2 As shown. Figure 2It can be seen that when M=2, the amount of ettringite generated in the system is the least, while the content of monosulfur calcium sulfoaluminate hydrate is the highest, which indicates that the low content of ettringite and the high content of monosulfur calcium sulfoaluminate hydrate are the main reasons for the low mechanical strength.
[0043] When M = 8, the mortar compressive strength of the system at 1d, 3d, 7d and 28d is 23.2MPa, 33.6MPa, 40MPa and 45.2MPa respectively. Compared with all other groups, the early and late strengths of the hardened matrix are very high when M = 8. The TG-DTG curves of all samples are shown in Figure 2. Figure 3 As shown. Figure 3 It can be seen that the amount of calcium sulfoaluminate generated in the system is not the highest when M=8, because the sulfate content in the system is the highest when M=10, resulting in the highest calcium sulfoaluminate content generated in the M=10 group. As for the content of monosulfur calcium sulfoaluminate hydrate, only a small amount is generated in the M= group, while the content of monosulfur calcium sulfoaluminate hydrate generated in M=8 is more than that in the M=10 group. However, the compressive strength of the M=8 group is higher than that of the M=10 group at any age, which shows that the more calcium sulfoaluminate content is not the better, and it is not conducive to the development of strength after exceeding a certain limit. On the whole, in practical applications, the calcium sulfoaluminate modified silicate cement prepared in Example 4 not only has high early strength, but also has no shrinkage in later strength.
[0044] Table 1 Mortar mix ratio of calcium sulphoaluminate modified silicate cement strength test described in Examples 1 to 5 (unit: g)
[0045]
[0046] The above embodiments describe the present invention and its implementation methods, which are not restrictive. The embodiments listed are only some of the implementation methods of the present invention, and the actual implementation methods are far from being limited thereto. Therefore, without departing from the purpose of the invention, any manufacturing method and embodiment similar to the technical solution of the present invention without creative design shall fall within the protection scope of the present invention.
Claims
1. A method for preparing calcium sulphoaluminate modified silicate cement based on thermodynamic calculation, characterized in that: The following steps are involved: Calcium sulphoaluminate modified silicate cement is composed of silicate clinker, sulphoaluminate clinker and anhydrous gypsum; The process diagram of the evolution of hydration products of the calcium hydroxide-anhydrous calcium sulfoaluminate-anhydrous gypsum ternary system over time was established through Gibbs energy minimization thermodynamic simulation software, and it was found that when the molar ratio of anhydrous gypsum / anhydrous calcium sulfoaluminate was M=8, no monosulfur type hydrated calcium sulfoaluminate was generated in the hydration products; based on the fact that calcium hydroxide is obtained by hydration of C3S and C2S, anhydrous calcium sulfoaluminate is provided by sulfoaluminate clinker, and the mineral phase compositions of a certain Portland cement clinker and a certain sulfoaluminate cement clinker are measured respectively, the proportion of calcium sulfoaluminate modified Portland cement can be inversely calculated.
2. The method for preparing calcium sulphoaluminate modified silicate cement based on thermodynamic calculation according to claim 1, characterized in that: The process diagram of the evolution of hydration products of the calcium hydroxide-anhydrous calcium sulfoaluminate-anhydrous gypsum ternary system over time was established using Gibbs energy minimization thermodynamic simulation software.
3. The method for preparing calcium sulphoaluminate modified silicate cement based on thermodynamic calculation according to claim 1, characterized in that: The silicate clinker does not contain gypsum; the sulphoaluminate clinker does not contain gypsum.
4. The method for preparing calcium sulphoaluminate modified silicate cement based on thermodynamic calculation according to claim 1, characterized in that: When M=8, no monosulfur type calcium sulfoaluminate hydrate is generated in the hydration product.
5. The method for preparing calcium sulphoaluminate modified silicate cement based on thermodynamic calculation according to claim 1, characterized in that: The calcium sulphoaluminate content in the raw material sulphoaluminate cement clinker used for preparation is greater than 60wt%.
6. The method for preparing calcium sulphoaluminate modified silicate cement based on thermodynamic calculation according to claim 1, characterized in that: The specific surface area of the raw material silicate cement clinker used in the preparation is 350m 2 / kg~450m 2 / kg, D 50 It is 10μm~50μm.
7. The method for preparing calcium sulphoaluminate modified silicate cement based on thermodynamic calculation according to claim 1, characterized in that: The specific surface area of the raw material sulphoaluminate cement clinker used in the preparation is 350m 2 / kg~450m 2 / kg; D 50 It is 10μm~50μm.
8. The method for preparing calcium sulphoaluminate modified silicate cement based on thermodynamic calculation according to claim 1, comprising the following steps: (1) Weigh the required raw materials such as silicate clinker, sulphoaluminate clinker and anhydrous gypsum according to the designed formula ratio of M value of 2 to 10, and stir them to mix them evenly; (2) slowly adding water to the powder mixed evenly in step (1), adding standard sand during the stirring process, stirring at high speed to form a plastic slurry, pouring it into a mold, and performing standard curing; (3) After demoulding, place in a standard curing box for curing.
